Prevalence of aortic stenosis and TAVR outcomes in patients with systemic sclerosis‐associated pulmonary hypertension. (24th August 2022) - Alman, Kirsten; Sadd, Corey J.; Ravel, Amish; Raza, Farhan; Chybowski, Amy; Runo, James R.
Abstract: There is little known about performing transcatheter aortic valve replacement (TAVR) in patients with group 1 pulmonary arterial hypertension (PAH) on advanced pulmonary vasodilator therapy. Retrospective cohort study among 90 patients with systemic sclerosis‐associated pulmonary arterial hypertension and systemic sclerosis‐associated pulmonary hypertension (SSc‐PAH/PH) evaluated at a tertiary PH center. The SSc‐PAH/PH cohort was stratified by the presence or absence of aortic stenosis (AS) to identify differences in baseline characteristics, hemodynamics, and long‐term outcomes. Of the 90 SSc‐PAH/PH patients, 13 patients were diagnosed with AS at PH diagnosis and another 6 patients developed AS during the study period. The period prevalence of AS was 21.1% (19/90, 95% confidence interval: 13.2%–30.1%) of which 94.7% was mild (18/19) at diagnosis with mean age at AS diagnosis of 66.3 + 2.2 years. Among AS patients, 31.6% (6/19) progressed to severe AS, five of which underwent TAVR (median age: 70 years) while on advanced PAH therapy. One of the five TAVR patients developed worsening pulmonary hypertension post‐TAVR. The 5‐year survival rate for all AS patients from diagnosis date was 37.2%. There was a high prevalence of AS in this cohort of SSc‐PAH/PH patients, with mean age of onset younger than patients with nonbicuspid aortic valve stenosis. This is the largest series of SSc‐PAH/PH patients on advanced pulmonary vasodilator therapy who underwent TAVR with acceptable early outcomes.